Perbandingan Komposisi Tepung Ubi Jalar Cilembu (Ipomoea batatas L.) dengan Tepung Terigu Terhadap Kualitas Krekers - Harefa, Thessalonika Elberta; Herawati, Maria Marina (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2024)
Crackers are a type of biscuit whose manufacture requires a fermentation process or not, as well as going through a lamination process to produce a flat shape and when broken the cross-section appears layered. The main ingredient in making crackers is wheat flour. With increasing prices and limitations in importing, local flour is needed which can help reduce the use of wheat flour and one of them is Cilembu sweet potato flour. This study aimed to determine the effect of the composition of Cilembu sweet potato flour (Ipomoea batatas L.) and wheat flour on the quality of crackers produced. The research method used was Randomized Block Design with 5 treatments, namely 100%T (use of 100% wheat flour), 25%U (use of 25% Cilembu sweet potato flour: 75% wheat flour), 50%U (use of 50 % Cilembu sweet potato flour: 50% wheat flour), 75%U (use of 75% Cilembu sweet potato flour: 25% wheat flour) and 100%U (use of 100% Cilembu sweet potato flour). The results showed that the substitution of wheat flour with Cilembu sweet potato flour had no significant effect on ash content, moisture content, carbohydrate content, and fat content. However, it had a significant effect on carotenoid content and protein content. The cracker produced also did not contain E. coli. The benefit of this research is that it can be an innovation and increase the use of local flour.